Enhancing students’ communication and collaboration skills through project-based learning in biology - Muhammad Isrul; Andi Asmawati Azis; Nurhayati B; Firdaus Daud; Muhiddin Palennari (JPBIO (Jurnal Pendidikan Biologi), 2026)
Biology learning requires mastery of concepts as well as communication and collaboration skills relevant to the 21st century. This study aims to analyze the effect of implementing deep learning-based Project-Based Learning (PjBL) compared to deep learning-based Direct Instruction (DI) on students’ communication and collaboration skills. The study employed a quasi-experimental method using a pretest-posttest nonequivalent control group design. The sample consisted of two 12th-grade classes at State High School 3 Makassar, selected through purposive sampling. The instruments consisted of validated questionnaires on communication and collaboration skills. Data were analyzed using ANCOVA at a significance level of 0.05. The results showed that the learning model had a significant effect on communication skills (F=53.59; p<0.05) and collaboration skills (F=8.89; p<0.05) after controlling for initial ability. The posttest average for communication in the PjBL class (84.81) was higher than that in the DI class (70.60), as was the case for collaboration (81.26 vs. 74.00). This study concludes that the deep learning-based PjBL model is more effective than the deep learning-based DI model in improving students’ communication and collaboration skills in biotechnology learning.